Comparison of self-collected vaginal swabs and first-void urine for detection of human papillomavirus in sexually active girls and women in three South Asian countries - Nigus Telele; Nishan Katuwal; Furqan Kabir; Sezanur Rahman; Sabin Bikram Shahi; Raja Ram Yadav; Fatima Aziz; Md Abir Hossain; Alexandra M. Hill; Indriana Permatasari; Yubin Lee; Haeun Cho; et al. (PLoS ONE, 2026)
Background As more countries plan and launch human papillomavirus (HPV) vaccination campaigns, a variety of self-sampling methods and assays have been used for detecting high-risk HPV (HR-HPV) types. This study compared HR-HPV detection in self-collected vaginal swabs (SCVS) and first-void urine (FVU) among sexually active girls and women aged 15–25 years in diverse settings (Bangladesh, Nepal, and Pakistan) using harmonized methods for each step. Methods Within the Global Burden Estimation of HPV (GLOBE-HPV) project, which aims to estimate HPV prevalence and incidence across eight low- and middle-income countries in South Asia and Sub-Saharan Africa, we analyzed paired SCVS and FVU samples from 753 participants in Bangladesh, Pakistan, and Nepal using standardized protocols. DNA was extracted using the QIAamp DNA Mini Kit, and HPV testing was performed with the Allplex HPV28 Detection PCR assay. We evaluated HPV detection and type-specific concordance using Cohen’s Kappa, McNemar’s test, and a 3 × 3 agreement table, along with accuracy and positive/negative agreement metrics. Results The overall prevalence of 14 HR-HPV types was 8.6% in SCVS and 7.2% in FVU samples. Detection rates for 7 HR-HPV vaccine types were similar (5.3% in SCVS versus 5.0% in FVU), with nearly identical HPV 16/18 rates (2.3% in SCVS and 2.4% in FVU). Bi-directional type-specific discordance was noted, with each sample type detecting unique types. SCVS demonstrated higher sensitivity for detecting HPV types beyond the 9 vaccine types with McNemar p-values of 0.013 and <0.001 for 14 and 28 types, respectively, while overall concordance remained high (Kappa >0.7). Samples with lower viral load (indicated by higher real-time PCR cycle threshold values) were more likely to yield discordant results. Conclusion SCVS and FVU yielded similar HR-HPV results, including those targeted by the 9-valent HPV vaccine, in sexually active young women. Both non-invasive self-sampling methods have potential for use in large-scale HPV surveillance programs in resource-limited settings.